Sistem Telemonitoring KWH Meter Menggunakan Modul Wi-Fi ESP8266 Berbasis Arduino Uno - Hidayat Nur Isnianto; Muhammad Arrofiq; Rijeqi Rahmawati; Bagus Mulyo Tyoso (Jurnal Rekayasa Elektrika, 2019)
The postpaid KWH Meter reading by officers is sometimes constrained to reach the physical KWH Meter because the house fence is locked or the KWH Meter is inside the house. This often causes problems such as reading errors and the officer must come to the customer several times. Therefore a telemonitoring system for KWH Meters is made through an online WiFi network to help officers record electricity usage for consumers. This system uses ACS712 current sensor, ZMPT101B voltage sensor, different phase sensor, RTC DS1307 as a timer and date, Arduino as a data processor, Micro SD Card for storing date, time, and sensor readings, LCD as a viewer, and transmitted with modules ESP8266 Wi-Fi to a smartphone or PC with a simple web display. The test results show that all components can function properly. ACS712 30A current sensor has an average error of 1%, and the ZMPT101B voltage sensor is capable of carrying out voltage readings in load or no load conditions with an average error of0.5% and a different phase sensor has an average error of 1% for resistive load and 4.2% for inductive loads of TL lights. Power measurements have an average error of 1.3% for 75W incandescent lamp loads and 300W irons. The ESP8266 Wi-Fi module emits a maximum of 15 meters when not blocked and 10 meters when blocked. All measurement data can be stored on the SD Card.